Social Media Addiction in Youth: Problematic Teenage Overuse and Body Image Issues (Journal of Science-Innovative Research in Uzbekistan, 2023)
The widespread existence of social media in the modern digital age has reshaped how we connect, share, and communicate. It has provided numerous benefits, including global connectivity and access to vast information resources. However, it has revealed a number of issues that require our attention. The purpose of this article is to investigate the phenomenon of social media addiction in teenagers and its intricate relationship to body image concerns. We hope that by learning more about these issues, we will be able to better understand the challenges that today's youth face in the digital landscape and develop strategies to address them.